Intracellular autofluorescence as a new biomarker for cancer stem cells in glioblastoma - Castro, Joana Isabel Martins Cosme Vieira (2021)
The identification of cancer stem cells (CSCs), which are implicated in tumor initiation, progression, therapy resistance, and relapse, is of great biological and clinical relevance. In glioblastoma (GBM), this is still a challenge, as no single marker is able to universally identify populations of GBM cancer stem cells (GSCs). Indeed, there is still controversy on whether biomarker-expressing cells fulfill the functional criteria of bona fide GSCs, despite being widely used. Here, we describe a novel subpopulation of autofluorescent (Fluo+) cells in GBM that bear all the functional characteristics of GSCs, including higher capacity to grow as neurospheres, long-term self-renewal ability, increased expression of stem cell markers, and enhanced in vivo tumorigenicity. Mechanistically, the autofluorescent phenotype is largely due to the intracellular accumulation of riboflavin, mediated by the ABC transporter ABCG2. In summary, our work identifies an intrinsic cellular autofluorescent phenotype enriched in GBM cells with functional stem cells features that can be used as a novel, simple and reliable biomarker to target these highly malignant tumors, with implications for GBM biological and clinical research.